Pleiotropic Effect of IL-6 Produced by B-Lymphocytes During Early Phases of Adaptive Immune Responses Against TB Infection - Linge, Irina; Tsareva, Anastasiya; Kondratieva, Elena; Dyatlov, Alexander; Hidalgo, Juan; Zvartsev, Ruslan; Apt, Alexander (Frontiers in Immunology, 2022)
The role of B cells migrating to the lung and forming follicles during tuberculosis (TB) inflammation is still the subject of debate. In addition to their antibody production and antigen-presenting functions, B cells secrete different cytokines and chemokines, thus participating in complex networks of innate and adaptive immunity. Importantly, lung B-cells produce high amounts of the pleiotropic gp130 cytokine IL-6. Its role during TB infection remains controversial, partly due to the fact that IL-6 is produced by different cell types. To investigate the impact of IL-6 produced by B cells on TB susceptibility and immune responses, we established a mouse strain with specific IL-6 deficiency in B cells (CD19cre-IL-6fl/fl, B-IL-6KO) on the B6 genetic background. Selective abrogation of IL-6 in B cells resulted in shortening the lifespan of TB-infected B-IL-6KO mice compare to the wild-type controls. We provide evidence that at the initial TB stages B cells serve as a critical source of IL-6. In the lung, the effect of IL-6 deficiency in B cells is associated rather with B and T cell functioning, than with macrophage polarization. TB-infected B-IL-6KO mice displayed diminished sizes of B cells themselves, CD4+IFN-γ+, Th17+, and CD4+CXCR5+ follicular T cell populations. The pleiotropic effect of B-cell-derived IL-6 on T-cells demonstrated in our study bridges two major lymphocyte populations and sheds some light on B- and T-cells interactions during the stage of anti-TB response when the host switches on a plethora of acquired immune reactions.